Oral Presentations 2020
DOI: 10.1136/spcare-2020-pcc.18
|View full text |Cite
|
Sign up to set email alerts
|

18 Are UK palliative care patients willing to participate in a trial of bispectral index (BIS) technology for assessing levels of consciousness? Findings from an exploration of feasibility for I-CAN-CARE

Abstract: between clinically assisted hydration and lower rates or delayed onset of delirium. Conclusion There is insufficient evidence to draw conclusions on the impact of clinically assisted hydration on quality of life in the last days of life. Further research should focus on populations who are in the very final days of life. There is a lack of studies in non-cancer populations, and a lack of evidence relating to communication with patients and families about this uncertain area of clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…AMK derived sub-themes and themes, and mapped relationships between these and the codes and categories, assisting interpretation and conceptualisation. These were discussed further with the Study Advisory Group, and reported in AMK’s thesis [ 42 ]. For the current paper we revisited the analysis and agreed some further refinement of the themes and sub-themes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…AMK derived sub-themes and themes, and mapped relationships between these and the codes and categories, assisting interpretation and conceptualisation. These were discussed further with the Study Advisory Group, and reported in AMK’s thesis [ 42 ]. For the current paper we revisited the analysis and agreed some further refinement of the themes and sub-themes.…”
Section: Methodsmentioning
confidence: 99%
“…However, all previous studies have obtained informed consent from patients/family members prior to using the technologies [ 39 – 41 ]. In contrast, our series of studies of the use of sedatives and BIS technology in palliative care in the UK included an exploratory study, investigating the acceptability of the technology in advance of introducing it into the clinical context, conducted as part of a doctoral project [ 42 ]. This study, reported here, explored the acceptability of trialling BIS in clinical practice through a qualitative investigation into what current patients, relatives of current patients, and bereaved relatives thought of this technology and its potential use with palliative care patients.…”
Section: Introductionmentioning
confidence: 99%